Penyusunan Buku Pedoman Kode Klasifikasi Arsip di Unit Kearsipan PT Semen Padang - Nova Yulistika; Elva Rahmah (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis paper contains a discussion of how to use the archive classification code at PT Semen Padang and the preparation of a guidebook for the use of archive classification codes at the PT Semen Padang Archives Unit. The preparation of this manual aims to assist employees at PT Semen Padang in using the archive classification code in accordance with their respective work units. The research method used in writing this thesis paper is a descriptive research method. Data collection techniques carried out by means of observation and interviews. The subject of data collection was through observation in the PT Semen Padang Archives Unit. Observation was carried out by looking at how the employee's understanding was in giving the classification code of the archive. Subsequently interviews were conducted with employees at the PT Semen Padang Archives Unit. The author conducts a question and answer session with employees directly regarding the use of the archive classification code, the constraints faced in using the classification code, and the solutions to these constraints. Based on these results it can be concluded that the preparation of the archival classification code guidebook is actually to assist employees in providing archival classification codes properly and correctly. In the archive classification code manual in the PT Semen Padang Archives Unit, it can be concluded that the steps in preparing the archive classification code manual are: (1) needs analysis, based on the needs of employees in using the archive classification code as well as efforts to overcome obstacles encountered. (2) product design, to find out what are the points that will be explained in the preparation of the archive classification code manual made in the form of a chart. (3) product compilation, the process of compiling the product manual is the use of archive classification codes. With the archive classification code manual in PT Semen Padang's Filing Unit, it can help employees to avoid finding errors in archiving and is easy to find again.Keywords: classification code, archive, guide book